1855 Cal. Stat. 152-53 - (:unkn) unknown (My University, 1855)
Ch. 127, §§ 1-3: Provided that a person who killed another in a duel with "a rifle, shot-gun, pistol, bowie-knife, dirk, small-sword, back-sword or other dangerous weapon" would pay the decedent's debts and be liable to the decedent's family for liquidated damages.
Keywords: DUELING